Design of a quality management system based on the ISO 9001-2015 standard at the La Inmaculada Bilingual Educational Unit in the city of Guayaquil - Yánez Flores, David Xavier; Araujo Ballestero, Alan Cristopher (Ingeniería Química y Desarrollo, 2022)
The objective of this research is the design of an ISO 9001:2015 quality management system for the Unidad Educativa Bilingüe de la Inmaculada, in order for the institution to continuously improve its academic proposal and achieve long-term sustained success. For this purpose, the diagnosis, prognosis and control to the prognosis of the different causes that lead to the lack of good quality management in the institution were carried out. The sample and the type of methodological tools used for data collection are described. The analysis of the data by sections, compliance and non-compliance and the general level of compliance of the organization is specified. The solution to the problem is presented with a SWOT analysis followed by the mission and vision, which underwent a reformulation to meet current needs, the quality objectives and the quality policy, principles and values are described.